CinéBreast-factors influencing the time to first metastatic recurrence in breast cancer: Analysis of real-life data from the French ESME MBC database. (February 2020) - Gougis, P.; Carton, M.; Tchokothe, C.; Campone, M.; Dalenc, F.; Mailliez, A.; Levy, C.; Jacot, W.; Debled, M.; Leheurteur, M.; Bachelot, T.; Hennequin, A.; et al.
Abstract: Purpose: The Time to First Metastatic Recurrence (TFMR) could be considered as an indirect reflection of the tumour growth kinetics which plays an important role in cancer. Molecular subtypes such as expression of estrogen receptor are known predictive factors of TFMR. The CinéBreast study aimed to identify predictive factors of the time to TFMR. Methods: The French Epidemiological Strategy and Medical Economics (ESME) Metastatic Breast Cancer (MBC) Database (NCT03275311) was used, which contains data from a cohort of metastatic breast cancer patients from 2008 to 2016 using retrospective data collection. It is a national multi-centre database. The impact of TFMR on overall survival (OS) since first metastasis was also evaluated. Results: Among 16 702 patients recorded in the ESME MBC database, 10 595 had an initially localised breast cancer with hormone receptor (HR) and HER2 status available, with a metastatic recurrence. Median follow up was 56 months. Median TFMR was 59 months (<24: 20%, 24–60: 31%, 60–120: 25%, >120: 24%). HER2+ and TNBC were respectively 4 times and 12 times ( p < 0.0001) more likely to have a recurrence within 2 years when compared to the luminal subgroup. Short TFMR and HR-/HER2-subtype significantly correlated with a poor OS in multivariate analysis. Some patients with MBC (20% in HER2+, 10% in ER+/HER2-and <5% in the ER-/HER2-) were long-term survivors in all 3 subgroups. Conclusions: In this large-scale real-life data study, patients with a TNBC metastatic recurrence had a shorter TFMR. Short TFMR significantly correlated with worse overall survival. Highlights: ESME is a large-scale real-life database of 16 702 metastatic breast cancer patients. A short time to first metastatic recurrence is associated with poor overall survival. Triple-negative tumours were more likely to recur early than HR+ and HER2+ tumours.